ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL SETARA PISA KONTEN GEOMETRI - Orin Asdarina; Masriyah Ridha (Prosiding Seminar Nasional USM, 2019)
The purpose of this study was to determine students’ mathematical reasoning abilities in solving PISA equivalent geometry content problems at the class VIII of SMP Negeri Unggul Tunas Nusa and these factors can influence students’ mathematical reasoning abilities in solving equivalent questions of PISA geometry content at the class VIII of SMP Negeri Unggul Tunas Nusa. The research design used in this study was descriptive research. The subjects in this study were 30 students from class VIII- SMP Negeri Unggul Tunas Nusa.  Data collection was obtained through the distributing of tests and interviews. From the results of the data analysis, it was concluded that the mathematical reasoning students’ ability in Solving on geometry content problems in class VIII of SMP Negeri Unggul Tunas Nusa was in the very low category. The ability of students’ on Mathematical reasoning at the indicator I was 21.56%, indicator II was 33.49%, indicator III was 16.11%, and indicator IV was 15.56%. The cause of the obstacles faced by students in solving geometry content material problems is that students were not accustomed to solving problems that were non-routine for students, a little bit complicated, and require a high level of problem solving as the questions given to students were equivalent to PISA problems . Mastery of the material is limited and cannot suitable to the concepts that have been studied with the problem being worked on.